2013
DOI: 10.1177/0278364912468357
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and analysis of the wheels’ steering mechanics for planetary exploration wheeled mobile robots moving on deformable terrain

Abstract: Due to the requirements of challenging planetary exploration missions with wheeled mobile robots (WMRs), the driving mechanics of WMRs’ wheels moving on the deformable terrain has been researched intensively, but the mechanics of the wheels’ steering is lacking research. Systematic steering experiments were carried out using a single-wheel testbed for wheels moving on a lunar soil simulant with different radii, widths, lug heights, and lug numbers under different vertical loads. The influence of the eccentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 34 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…They proposed an equation for obtaining optimal grouser spaces that depend on geometric parameters (wheel radius, grouser height and spacing) and operating parameters (slip ratio and wheel sinkage). Ding et al experimentally confirmed the effects of the lug on the steering performance of the wheel [5].…”
Section: Introductionmentioning
confidence: 92%
“…They proposed an equation for obtaining optimal grouser spaces that depend on geometric parameters (wheel radius, grouser height and spacing) and operating parameters (slip ratio and wheel sinkage). Ding et al experimentally confirmed the effects of the lug on the steering performance of the wheel [5].…”
Section: Introductionmentioning
confidence: 92%
“…Lateral slip sinkage is more severe for narrower wheels [36]. Table 2 Terrain property parameters [32]. Parameters k c , k φ , and n slightly differ from those in [32] as a negative value of k c was accepted without being set to zero.…”
Section: Dynamic Sinkage Caused By Flow Of Deformable Soilmentioning
confidence: 99%
“…Table 2 Terrain property parameters [32]. Parameters k c , k φ , and n slightly differ from those in [32] as a negative value of k c was accepted without being set to zero. The value of k φ ismuch larger than |k c |; the equivalent sinkage exponent K s = k c /b + k φ for wheels with smaller width is slightly larger.…”
Section: Dynamic Sinkage Caused By Flow Of Deformable Soilmentioning
confidence: 99%
“…Inotsume et al (2013) constructed the empirical studies for analysing and controlling the rovers to reconfigure themselves to adapt to the target terrain that involves sandy slopes. Ding et al (2013) established a deformable terrain based experimental platform for analysing and evaluating the rover wheel steering performance and mechanics laying background for optimal design of rover steering mechanisms. In addition, Michaud et al (2006) developed a rover chassis evaluation tool for the design, selection and optimisation of chassis for space exploration rovers.…”
Section: Introductionmentioning
confidence: 99%